The Indo-Europeans archaeology, language, race, and the search for the origins of the West - Demoule, Jean-Paul 1947- (Oxford University Press, 2023)
The existence of an Indo-European linguistic family, allowing for the fact that several languages widely dispersed across Eurasia share numerous traits, has been demonstrated for several centuries now. But the underlying factors for this shared heritage have been fiercely debated by linguists, historians, archaeologists, and anthropologists. The leading theory, of which countless variations exist, argues that this similarity is best explained by the existence, at one given point in time and space, of a common language and corresponding population. This ancient, prehistoric, population would then have diffused across Eurasia, eventually leading to the variation observed in historical and modern times. The Indo-Europeans: Archaeology, Language, Race, and the Search for the Origins of the West argues that despite its acceptance and use by most researchers from different disciplines, such a model is inherently flawed. This book describes how, beginning in the late eighteenth century, Europeans began a quest for a supposed original homeland, from which a small conquering people would one day spread out, bringing their language to Europe and parts of Asia (India, Iran, Afghanistan). This quest was often closely tied to ideological preoccupations and it was in its name that the Nazi marc:leadership, claiming for the Germans the status of the purest Indo-Europeans (or Aryans), waged genocide. The last part of the book summarizes the current state of knowledge and current hypotheses in the fields of linguistics, archaeology, comparative mythology, and genetics. The culmination of three decades of research, this book offers a sweeping survey of the historiography of the Indo-European debate and poses a devastating challenge to the Indo-European origin story at its roots
Keywords: Geschichte 1814-2017; Rassentheorie; Indogermanen; Zivilisation; Indogermanische Sprachen; Anatolien